From no-knead to sourdough : a simpler approach to handmade bread - Miller, Victoria Redhed (New Society Publishers, 2018)
"Allows home bakers of any experience level to find their own "comfort zone" with bread-making. From simple no-knead yeast breads to breads using pre-ferments and sourdough starters, anyone can make bread on their own schedule, using equipment they already have, and ingredients that are readily available, and truly enjoy the process!"--Provided by publisher.